Happiness quantified a satisfaction calculus approach - Praag, Bernard M. S. van.; Ferrer-i-Carbonell, Ada. (Oxford : Oxford University Press, 2008)
How do we measure happiness? Focusing on subjective measures as a proxy for welfare and well-being, this book finds ways to do just that.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Satisfaction; Happiness